Federalism and globalization - Hueglin, Thomas O. (2001)
In the context of what is generally referred to as a globalizing world, we have become accustomed to speak of new forms of multilevel governance. The paradigmatic shift from government to governance signals the presumable end of the modern Westphalian state system in which the governments of territorial nation-states held exclusive or sovereign governing powers (Hueglin 1999). Instead, we now detect that acts of governing are carried out by a plurality of governmental and nongovernmental actors below and above the nation-state. Since these acts, by international organizations as well as regional governments and civic movements, affect citizens directly, a growing democratic deficit of accountability has been recognized. Democratic political theory and practice therefore have begun a search for viable models of global democratic governance. By recognizing territorial group rights alongside with individual rights and freedoms, federalism, or, more precisely, the theory and practice of the modern federal state, provide such a model in principle. This is by no means undisputed. In his search for models of cosmopolitan democracy, David Held, perhaps the most prominent global democracy theorist at the moment, had to admit that he substituted “federal” for “cosmopolitan” because of the controversial meaning of federalism in Europe (1992), and especially so in Britain where federalism, with the American model in mind, was seen as synonymous with federal government and centralization. In newly federalizing polities, however, Spain, Belgium and South Africa among others, federalism is understood as a safeguard of local and regional autonomy, or, more generally, as a means to the organized recognition of territorial group rights and their democratic inclusion into the body politic. In the context of globalization, it would have to mean both, as it of course always does, the establishment of effective and democratic governance on a world scale, and at the same time the retention of significant levels of autonomy and self-government for states, regions, localities and other collective actors. In this presentation I want to address three questions: 1. What exactly is globalization and does it exist? 2. What exactly is federalism and why do we need it? 3. What kind of federal institutions can serve global governance?